Listening to the voices of dissent: bridging political polarization through imagined dialogue. Issue 6 (1st November 2020) - Dashew, Brian; Grossman, Karen Doyle; Lawrence, Randee
ABSTRACT: This paper describes the authors' exploration of an arts-based practice, called imagined dialogue, as a means for engaging in reflective discourse in the current, global context of political polarization. We introduce the practice of imagined dialogue, taking the readers along on our continued learning journey of the implications of this practice for educational contexts. We highlight the connections of imagined dialogue to the theory and practice of transformative learning. This paper suggests that writing and embodying imagined dialogue can prepare people for real dialogue, allowing them to more deeply understand their own positions, as well as to empathize with and respect the positions of others. In addition to introducing the theoretical background and steps to engaging in the imagined dialogue process, we share several examples; including our own experiences using imagined dialogue in personal contexts, and group processing of a dialogue about an issue of national political significance. Using imagined dialogue is a skill that can be learned and strengthened, enabling learners to engage in and model the practice of critical, reflective discourse over time – even in the emotionally charged political sphere.